TRAINING NEEDS OF BROILER BREEDERS IN FIELDS OF (MANAGEMENT, AND MARKETING) IN DUHOK GOVERNORATE AND ITS RELATION WITH SOME VARIABLES - A. TAHA , ISMAIL.; AL-DOSKI, ABID ALI HASAN (Journal of Duhok University, 2020)
The main objective of the study was to assess the training needs of broiler breeders in Duhok governorate, and to find the relationship between selected characteristics and training needs. The research sample included 153 breeders representing 76.5% of the research population. Data used for the study were obtained using structured questionnaire and personal interviews. SPSS software were used to analyze the data collected, statistics such as frequency, percentage, mean, standard deviation, correlation were used.  The result shows that 43.1 % of the respondents need extensive training in all the studied areas (marketing and management) and there is a significant correlation between the need for training and the independent variable (ownership) and no significant relationship between training needs and  each of (age, Educational level, Number of years of experience in broiler breeding, and participation in training). In the light of the study findings, it was recommended that Agricultural extension in Duhok governorate should organize regular training for broiler breeders in the studied areas.